The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000492343
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of microRNA-133a Expression and Its Clinicopathologic Significance in Non-Small Cell Lung Cancer: A Comprehensive Study Based on Meta-Analysis and the TCGA Database

Abstract: Background: The role of microRNA-133a (miR-133a) in non-small cell lung cancers (NSCLCs) is controversial. Thus, we conducted a comprehensive study based on meta-analysis and The Cancer Genome Atlas (TCGA) database. Methods: Publications were searched in both English and Chinese databases, and meta-analysis was performed using Stata 12.0. The clinical value of miR-133a in NSCLC was investigated by collecting and calculating data from the TCGA database, and the statistical analysis was performed in R 3.5.0. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…The combination of miR-133a and FOBT could be a potential detection mode in colorectal cancer screening [83]. Based on the information from The Cancer Genome Atlas (TCGA) database and Metaanalysis results, along with bioinformatics analysis, miR-133a was recognized as a potential biomarker of NSCLC [84][85][86], oral cancer [87,88], osteosarcoma [89], cervical cancer [90], prostate cancer [91], digestive tumors [92] including EC [93][94][95], GC [96,97], pancreatic ductal adenocarcinoma (PDAC) [98] and CRC [99]. A study of 8006 tumors including 19 tumor types suggested that hypoxia contributed to genomic instability.…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…The combination of miR-133a and FOBT could be a potential detection mode in colorectal cancer screening [83]. Based on the information from The Cancer Genome Atlas (TCGA) database and Metaanalysis results, along with bioinformatics analysis, miR-133a was recognized as a potential biomarker of NSCLC [84][85][86], oral cancer [87,88], osteosarcoma [89], cervical cancer [90], prostate cancer [91], digestive tumors [92] including EC [93][94][95], GC [96,97], pancreatic ductal adenocarcinoma (PDAC) [98] and CRC [99]. A study of 8006 tumors including 19 tumor types suggested that hypoxia contributed to genomic instability.…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…A previous study showed that the incidence of MODS in patients with paraquat poisoning was ~84% (6). miRNAs are regulatory factors that play crucial roles in regulating growth, maintaining homeostasis of organisms and mediating various pathophysiological processes of diseases, and have become important research topics (35)(36)(37). The present bioinformatics results suggested that miR-27a may be a potential regulator for IL-10, thus indicating the potential role of miR-27a in paraquat poisoning.…”
Section: Discussionmentioning
confidence: 61%
“…Considering the poor prognosis of advanced CCA, the present study aimed to improve CCA outcomes through the assessment of a miRNA considered to be an independent prognostic factor. A number of studies have demonstrated that miRNAs are abnormally expressed in various cancer types, such as non-small cell lung (23), bladder (24) and colorectal (25) cancer and osteosarcoma (26), and have broad potential for use as diagnostic or/and prognostic markers and therapeutic targets for cancer treatment (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%